2009
DOI: 10.1016/j.csda.2008.02.032
|View full text |Cite
|
Sign up to set email alerts
|

The use of plasmodes as a supplement to simulations: A simple example evaluating individual admixture estimation methodologies

Abstract: With the advent of powerful computers, simulation studies are becoming an important tool in statistical methodology research. However, computer simulations of a specific process are only as good as our understanding of the underlying mechanisms. An attractive supplement to simulations is the use of plasmode datasets. Plasmodes are data sets that are generated by natural biologic processes, under experimental conditions that allow some aspect of the truth to be known. The benefit of the plasmode approach is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
(66 reference statements)
0
36
0
Order By: Relevance
“…Several articles (reviewed in Putman and Carbone ) have pointed out that the number of loci required for separating pure individuals from recent hybrids (F1, F2, backcrosses) is much higher than what is typically used in empirical studies (Fitzpatrick ; Vähä and Primmer ) and requires carefully designed sampling schemes including pure individuals (Vaughan et al. ). It is thus uncertain that the low level of nuclear introgression that goes with mitochondrial introgression in some of our simulations (truea¯ as low as 0.19–0.25) would be easily identified in all empirical studies where mito‐nuclear discordance have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles (reviewed in Putman and Carbone ) have pointed out that the number of loci required for separating pure individuals from recent hybrids (F1, F2, backcrosses) is much higher than what is typically used in empirical studies (Fitzpatrick ; Vähä and Primmer ) and requires carefully designed sampling schemes including pure individuals (Vaughan et al. ). It is thus uncertain that the low level of nuclear introgression that goes with mitochondrial introgression in some of our simulations (truea¯ as low as 0.19–0.25) would be easily identified in all empirical studies where mito‐nuclear discordance have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Vaughan et al. () examined an experimental cross of mice and found that 11 microsatellite loci were generally insufficient for correctly inferring admixture when individuals from the founding subpopulations were not included in the analysis. When a large proportion of individuals in the dataset are admixed, Pritchard et al.…”
Section: Population Structurementioning
confidence: 99%
“…The problem of too few loci can be particularly troublesome when inferring admixture. Vaughan et al (2009) examined an experimental cross of mice and found that 11 microsatellite loci were generally insufficient for correctly inferring admixture when individuals from the founding subpopulations were not included in the analysis. When a large proportion of individuals in the dataset are admixed, Pritchard et al (2000) observed that estimates of ancestry coefficients may only be reliable for a large number of loci.…”
Section: Weak Structurementioning
confidence: 99%
“…As an alternative to simulation, Vaughan et al (Vaughan et al, 2009) suggested creating “plasmode” datasets. A plasmode is a real dataset that is created from natural processes but has some aspect of the data-generating model known, for example, a “spike-in” experiment in microarray analysis of gene expression where a known amount of genome transcript is added to each sample.…”
Section: Introductionmentioning
confidence: 99%